Analisis Produktivitas Pengolahan Minyak Kelapa Sawit Dengan Metode Marvin E. Mundel (Studi Kasus: PTPN V Sungai Pagar Kecamatan Kampar Kiri Kabupaten Kampar) - Yuza Elfa Lestari; Ahmad Rifai; Didi Muwardi (Politeknik Pertanian Negeri Payakumbuh, 2019)
This research aims to know the productivity of palm oil processing, evaluated the productivity and give solutions improved productivity of palm oil processing in PTPN V Sungai Pagar district of Kampar Kiri Kampar Regency. The productivity measurement method used is the Marvin E. Mundel method. Measurement of productivity by setting the month of January 2016 as the basis period of the partial results obtained the highest productivity index of 160.13percents February 2017 for depreciation, amounting to 132.16percents July 2016 for materials, amounting to 258.26percents January 2017 for labor, of 273.12percents January 2017 for energy, amounted to 263.04percents and September 2016 for maintenance.While the lowest partial productivity index of 93.93percents December 2017 for depreciation, amounting to 94.07percents February 2017 for the material, to 65.00percents June 2016 for labor, of 66.25percents, June 2016 for energy, and of 67.43percents April 2016 for maintenance. The highest total productivity index was reached in February, 2017 of 133.70percents and lowest in February 2016 of 94.24percents. Solutions for increasing the productivity of palm oil processing: 1) increasing the number of FFB processed by paying attention to the quality of the fruit to be received 2) improving control of employee work, 3) making service schedules for PKS machines and equipment, 4) processing activities carried out in accordance with the maximum hours of processing PKS, 5) repair of production floor and loading ramp, 6) hold socialization in KUD/farmer groups and communities around PKS area, 7) improve company relations with partners, and 8) make improvements to the division of work shifts.